Prevalence of Leprosy in District Buner, Khyber Pakhtunkhwa, Pakistan - Sana Ulfat, Bashir Khan, Muhammad Khubaib, Kausar Saeed, Faridullah Shah, Hafiz Mahmood Azam, Samrah Masud, Syed Zain Zaffar Bukhari, Assad Ullah, Hameed Ur Rehman (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Leprosy, commonly referred to as Hansen’s disorder, is caused by the obligatory intracellular acid-fast bacilli Mycobacterium leprae and is predominantly transmitted by inhalation macrophages. It causes infection of the skin and nerves, as well as neurological damage due to inflammation. Aim: The current study was conducted to determine the prevalence of leprosy disease in District Buner, Khyber Pakhtunkhwa, Pakistan.During the investigation, we reported different types of leprosy. Methods: The current study investigates 467 patients from 1965-2000 in six Tehsil and 74 from 2000-2021. In the reported five types of Leprosy, Lepromatous Leprosy is more common than other types. Leprosy has five subtypes which 2 are Tuberculoid (TT), Lepromatous Leprosy (LL), and 3 are borderline types Leprosy Borderline tuberculoid (BT), Borderline (BB),borderline lepromatous (BL). Results: In the study area,the Lepromatous type of leprosy was abundant in the population of district Buner. The percentage of lepromatous leprosy from 2000 to 2021 is 38%, Borderline 9.5%, Borderline tuberculoid 31%, Borderline lepromatous 18%, Tuberculoid Leprosy 3%, Tuberculoid Borderline 3.1%. Leprosy disease is primarily reported in the male population as compared to females. Now we classified leprosy into two groups which are multibacillary and paucibacillary. Paucibacillary (PB) are single lesion paucibacillary and those with two to five lesions. Multibacillary (MB) with six or more lesions. We determined the age-wise distribution of the percentage of patients with ages of 20-40 years 70.5% males, 29.4% females, age of 40-60 years, 58.0% males and 29.0% females, age of 60-80, 58.6% males and 14.2 % females, age of 80-94 in which 100% males and 0% females and age of 111 are only one patient male 100% and female 0%. We also investigated the Tehsils-wise distribution of patients from 2000 to 2021. Tehsil Dagger consists of 36% of patients, and Tehsil Gadezai consists 19%, Tehsils Mandan consists of 14%, Tehsil Khudukhail consists 2%, Tehsil Salarzai consists of 17% and Tehsil Chagarzai 12%. Practical Implication: The significance of the present study to find the demographic influences related with leprosy, analyze the prevalence of leprosy among different age groups, assess the awareness and knowledge about leprosy among people living and investigate any health services available to people affected by leprosy. Conclusion: The current study was conducted to determine the prevalence of leprosy disease in District Buner, Khyber Pakhtunkhwa, Pakistan. During the investigation, we reported different types of leprosy. Now we classified leprosy into two groups which are multibacillary and paucibacillary. Paucibacillary (PB) are single lesion paucibacillary and those with two to five lesions. Multibacillary (MB) with six or more lesions. Keywords: Leprosy; Mycobacterium leprae; Multibacillary; Paucibacillary; Prevalence; Buner